Research and Design of Vehicle Control Unit (VCU) Based on TCN - 肖家博; 黎福海; 杨卫峰; 易伟民; 宁侨 (机车电传动)
This paper described the VCU composition of communication system, system solutions for VCU hardware platform, system design method for VCU software platform and main function of VCU. The field application of the VCU shows that the VCU has powerful function, stable performance and high reliability.